Signaling related with biphasic effects of bisphenol A (BPA) on Sertoli cell proliferation: A comparative proteomic analysis - Ge, Li-Chen; Chen, Zhuo-Jia; Liu, Hao; Zhang, Kun-Shui; Su, Qiao; Ma, Xiang-Yu; Huang, Hong-Bin; Zhao, Zhen-Dong; Wang, Yu-Ye; Giesy, John P.; Du, Jun; Wang, Hong-Sheng (Biochimica et biophysica acta, 2014)
Biphasic effects on cell proliferation of bisphenol A (BPA) can occur at lesser or greater exposures. Sertoli cells play a pivotal role in supporting proliferation and differentiation of germ cells. The mechanisms responsible for inverse effects of great and low concentrations of BPA on Sertoli cell proliferation need further study. We utilized proteomic study to indentify the protein expression changes of Sertoli TM4 cells treated with 10−8M and 10−5M BPA. The further mechanisms related to mitochondria, energy metabolism and oxidative stress were investigated by qRT-PCR and Western-blotting analysis. Proteomic studies identified 36 proteins and two major clusters of proteins including energy metabolism and oxidative stress expressed with opposite changes in Sertoli cells treated with 10−8M and 10−5M BPA, respectively, for 24h. Exposure to 10−5M BPA resulted in greater oxidative stress and then inhibited cell proliferation, while ROS scavenger NAC effectively blocked these effects. Exposure to 10−8M BPA caused higher intercellular ATP, greater activities of mitochondria, and resulted in significant proliferation of TM4 cells, while oligomycin A, an inhibitor of ATP synthase, abolished these growth advantages. Our study demonstrated that micromolar BPA inhibits proliferation of Sertoli cells by elevating oxidative stress while nanomolar BPA stimulates proliferation by promoting energy metabolism. Micromolar BPA inhibits cell proliferation by elevating oxidative stress while nanomolar BPA stimulates cell proliferation by promoting energy metabolism. Our study demonstrates, for the first time, that micromolar BPA inhibits proliferation of Sertoli cells by elevating oxidative stress while nanomolar BPA stimulates proliferation of cell by promoting energy metabolism. [Display omitted] •Nanomolar BPA stimulated proliferation of TM4 cells.•Micromolar BPA inhibited proliferation of TM4 cells.•ROS scavenger effectively blocked inhibitory effects of 10−5MBPA.•ATP synthesis inhibitor abolished growth advantages provided by 10−8MBPA.